2017
DOI: 10.2147/ndt.s144788
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal sensitivity mediates the effects of child abuse and affective temperaments on depressive symptoms in the general adult population

Abstract: BackgroundRecent studies have suggested that multiple factors interact with the onset and prognosis of major depressive disorders. In this study, we investigated how child abuse, affective temperaments, and interpersonal sensitivity are interrelated, and how they affect depressive symptoms in the general adult population.Subjects and methodsA total of 415 volunteers from the general adult population completed the Patient Health Questionnaire-9, the Temperament Evaluation of Memphis, Pisa, Paris, and San Diego-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 36 publications
3
30
0
Order By: Relevance
“…As expected from the results of previous studies showing that early experiences in childhood affect personality traits (6,8,9,20,(46)(47)(48)(49)(50)(51), parental care in childhood increased resilience and parental overprotection decreased it in this study. Consistent with our results, Lind et al reported the same findings, and also demonstrated that the interaction of childhood sexual abuse with high parental authoritarianism affected resilience (17).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As expected from the results of previous studies showing that early experiences in childhood affect personality traits (6,8,9,20,(46)(47)(48)(49)(50)(51), parental care in childhood increased resilience and parental overprotection decreased it in this study. Consistent with our results, Lind et al reported the same findings, and also demonstrated that the interaction of childhood sexual abuse with high parental authoritarianism affected resilience (17).…”
Section: Discussionsupporting
confidence: 90%
“…Our results replicated the results of Lind et al and further demonstrated that resilience mediated the effect of perceived parental bonding on work stress. Such a mediating effect of resilience has never been reported to date, but it is plausible considering that resilience is a type of positive personality trait; mediating effects between early experiences and life events or psychopathological symptoms have been shown for various personality traits (6,8,9,(48)(49)(50)(51). A previous systematic review showed that amenable resilience-enhancing factors moderate and/or mediate the association between childhood adversity and mental health in young people (16).…”
Section: Discussionmentioning
confidence: 99%
“…Vulnerability characteristics mediate the effect of childhood maltreatment on incident mental disorders [15]. Interpersonal sensitivity mediates the effect of childhood maltreatment on depression in adulthood [16]. In addition, trait anxiety mediates the effect of child maltreatment on depression in adulthood [17].…”
Section: Discussionmentioning
confidence: 99%
“…The influence of childhood maltreatment on depression is mediated by several factors. Interpersonal sensitivity and trait anxiety mediate the influence of childhood maltreatment on depression in adulthood [16,17]. Various factors influence the relationship between childhood maltreatment and adulthood depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that affective temperaments affect depressive symptoms in general adults. 10 , 11 , 32 In addition, subjective cognitive function is influenced by depressive symptoms, quality of life, ability to work, medical or psychiatric comorbidity, and medication use. 17 , 19 , 21 A previous study suggests that individuals with hyperthymic temperament may have better functional recovery.…”
Section: Discussionmentioning
confidence: 99%